FOXM1 expression reverts aging chromatin profiles through repression of the senescence-associated pioneer factor AP-1 - Fábio J. Ferreira; Mafalda Galhardo; João M. Nogueira; Joana Teixeira; Elsa Logarinho; José Bessa (Nature Communications)
Abstract Aging is characterized by changes in gene expression, some of which can drive deleterious cellular phenotypes and senescence. The transcriptional activation of senescence genes has been mainly attributed to epigenetic shifts, but the changes in chromatin accessibility and its underlying mechanisms remain largely elusive in natural aging. Here, we profiled chromatin accessibility in human dermal fibroblasts (HDFs) from individuals with ages ranging from neonatal to octogenarian. We found that AP-1 binding motifs are prevalent in elderly-specific accessible chromatin regions while neonatal-specific regions are highly enriched for TEAD binding motifs. We further show that TEAD4 and FOXM1 share a conserved transcriptional regulatory landscape controlled by a not previously described and age-dependent enhancer that loses accessibility with aging and whose deletion drives senescence. Finally, we demonstrate that FOXM1 ectopic expression in elderly cells partially resets chromatin accessibility to a youthful state due to FOXM1’s repressive function on several members of the AP-1 complex, which is known to trigger the senescence transcriptional program. These results place FOXM1 at a top hierarchical level in chromatin remodeling required to prevent senescence.